Toward a tourism destination brand equity of coastal tourism of Pangandaran Regency - Ibrahim Rashid (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
Indonesia is one of the countries where tourism is the major contributors to the GDP. There are province and districts in Indonesia that mainly focused on the tourism business, Pangandaran is one of them. As a new district, Pangandaran is still trying to develop its brand as a tourist destination. This study aims to provide perceptual maps of Pangandaran as a brand compared to other coastal tourism destination. The study used Multidimensional Scaling (MDS), to inquire about the brand image of various coastal destination in Indonesia among domestic tourist. Two dimensions consisted of performance and value are used to measure the destination brand. More profound questions are also asked to inquire about factors that may influence tourist visitation. The result indicates that the Pangandaran brand as a tourism destination is perceived as a domestic oriented destination. A suggestion based on five steps of brand building is proposed to improve Pangandaran